Evaluasi Energi Metabolis Pakan Lokal Pada Ayam Petelur - Syaiful Bahri; Rusdi Rusdi (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
Evaluation of metabolically energy of three agricultural by-products has been conducted on laying hens. The purpose of study was to calculate and to compare the energy values of onion hay, tofu waste and bananas skin. Twelve laying hens were randomly allocated to one out of three types of feeds. About 50 g of powder form of feeds were forced fed to the experimental hens. The results indicate that the gross energy varied within the tested feeds. The highest values of apparent metabolically energy (AME) and true metabolically energy (TME) were achieved by tofu waste, while the energy (AME and TME) values of onion hay were higher than those values in bananas skin. The values of TME were 10.04, 11.88 and 9.58 MJ/kg for onion hay, tofu waste and bananas skin, respectively. It is concluded that the by-product feeds are still having metabolically energy as feeds sources for raising chickens, particularly laying hen